2018
DOI: 10.1186/s12888-018-1793-9
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in the treatment of Lithium-induced nephrogenic diabetes insipidus: the protocol of a randomized controlled trial

Abstract: BackgroundLithium is the gold-standard treatment for bipolar disorder, is highly effective in treating major depressive disorder, and has anti-suicidal properties. However, clinicians are increasingly avoiding lithium largely due to fears of renal toxicity. Nephrogenic Diabetes Insipidus (NDI) occurs in 15–20% of lithium users and predicts a 2–3 times increased risk of chronic kidney disease (CKD). We recently found that use of statins is associated with lower NDI risk in a cross-sectional study. In this curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Data will be used from a pre-existing large double blind RCT conducted on lithium users to assess the effect of atorvastatin (20 mg/day) vs placebo on lithium induced NDI in patients with BD ( n = 54) and MDD ( n = 6). This double-blind RCT (Clinicaltrials.gov ID: NCT02967653) was conducted over a 12-week period [ 26 28 ]. For this secondary analysis, the RCT data will be used to assess whether atorvastatin versus placebo can reduce calcium levels in lithium users with BD and MDD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data will be used from a pre-existing large double blind RCT conducted on lithium users to assess the effect of atorvastatin (20 mg/day) vs placebo on lithium induced NDI in patients with BD ( n = 54) and MDD ( n = 6). This double-blind RCT (Clinicaltrials.gov ID: NCT02967653) was conducted over a 12-week period [ 26 28 ]. For this secondary analysis, the RCT data will be used to assess whether atorvastatin versus placebo can reduce calcium levels in lithium users with BD and MDD.…”
Section: Methodsmentioning
confidence: 99%
“…Participants not meeting this criteria were excluded from the study. A sample of n = 60 participants will allow an effect size of 0.34 at two-tailed alpha = 0.05 and Power (1-Beta) =0.8 [ 28 ]. For the detailed study methodology and Consort Diagram, refer to the study protocol and the original RCT [ 26 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have provided individual descriptions of the methods of each study below. Specific inclusion or exclusion criteria of the studies have been previously reported [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes is a public health issue of general concern around the world. It is a lifelong chronic disease that can affect multiple organs; it is the third most common, frequently-occurring, and chronic non-communicable disease after cerebrovascular disease and tumors; and it poses a serious threat to human health ( 2 ). Statistics show that there are about 347 million patients suffering from diabetes mellitus type 2 (T2DM) in the world so far, and its prevalence in low-income countries is more serious ( 3 ).…”
Section: Introductionmentioning
confidence: 99%